Does intensity or youth affect the neurobiological effect of exercise on major depressive disorder?. (January 2018) - Budde, Henning; Velasques, Bruna; Ribeiro, Pedro; Machado, Sergio; Emeljanovas, Arunas; Kamandulis, Sigitas; Skurvydas, Albertas; Wegner, Mirko
Abstract: The purpose of this commentary is to discuss the different neurobiological effects of exercise on major depressive disorder (MDD) in children and adolescents and to provide additional explanations to this well written systematic review. This commentary highlights the effects of exercise on the hypothalamic-pituitary-adrenal (HPA) axis, which plays a crucial role in MDD. We address the questions of whether age and different exercise intensities may provide additional information on the neurobiological effects of acute or chronic exercise on MDD. Previous findings clearly suggest that the etiology of MDD is complex and multifaceted, involving numerous neurobiological systems, which are additionally influenced by these two factors.